Differential evolution technique of HEPWM for three-phase voltage source inverter - Azziddin, Mohamad Razali; Kamisman, Norazelina; Jurifa, Mat Lazi; Bahari, Norhazilina (Asian Research Publishing Network (ARPN), 2016)
This paper presents the execution of Differential Evolution (DE) algorithm in order to understand the principle operation of Harmonic Elimination Pulse-Width Modulation (HEPWM) switching technique. HEPWM utilizing the DE technique is proposed to eliminate low frequency harmonic components of three-phase inverter output voltage. Explanation of DE algorithm execution is given and the best approach of mutation strategy used in DE has been investigated. Switching angles of HEPWM are calculated offline by using the DE technique. Subsequently, the calculated switching angles are used to operate the three-phase voltage source inverter. Computation of DE algorithm and simulation of voltage source inverter using the calculated switching angles are carried out by using Matlab/Simulink software package. Simulation results show the effectiveness of proposed DE technique in eliminating the low order harmonic components of output voltage for three-phase voltage source inverter.